Pengaruh Online Costumer Review, Dan Online Customer Rating Terhadap Keputusan Pembelian Melalui Marketplace Shopee pada Mahasiswa Prodi Manajemen Feb Universitas Panca Bhakti Pontianak - Anggelina Liberty, Gloria; Untung Utama, Naiyun (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2024)
This research aims to find out how much influence online customer reviews and online customer ratings have on purchasing decisions via the Shopee marketplace among FEB Management Study Program students, Panca Bhakti University, Pontianak. This research uses quantitative methods, with a population of management study program students from Panca Bhakti University, Pontianak who carry out online transactions on the Shopee marketplace and a sample of 130 respondents using purposive sampling. The test tools used are Validity, Reliability, Normality, Heteroscedasticity, Multicollinearity, coefficient of determination (Adjusted R), t test, and F test. The analysis technique uses multiple linear regression analysis, supported by statistical tests, using the SPSS version 23 program. Based The results of multiple linear regression analysis obtained a sig of Online Customer Review 0.000 < 0.05 and Online Customer Rating 0.000 < 0.05, meaning that Online Customer Review partially influences purchasing decisions, and Online Customer Rating partially influences purchasing decisions.